2019
DOI: 10.2196/14696
|View full text |Cite
|
Sign up to set email alerts
|

Cash Transfer to Adolescent Girls and Young Women to Reduce Sexual Risk Behavior (CARE): Protocol for a Cluster Randomized Controlled Trial

Abstract: Background The HIV epidemic in Eastern and Southern Africa is characterized by a high incidence and prevalence of HIV infection among adolescent girls and young women (AGYW) aged 15-24 years. For instance, in some countries, HIV prevalence in AGYW aged 20-24 years exceeds that in AGYW aged 15-19 years by 2:1. Sauti (meaning voices), a project supported by the United States Agency for International Development, is providing HIV combination prevention interventions to AGYW in the Shinyanga region, Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…In addition, a 2018 metaanalysis of studies done in sub-Saharan Africa on linkage to care following CB-HCT showed that levels of linkage ranged from 10% to 79% [14]. In other settings, linkage to care at individual levels was influenced by fear of not being able to continue with livelihood if one's status were to be known [23].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a 2018 metaanalysis of studies done in sub-Saharan Africa on linkage to care following CB-HCT showed that levels of linkage ranged from 10% to 79% [14]. In other settings, linkage to care at individual levels was influenced by fear of not being able to continue with livelihood if one's status were to be known [23].…”
Section: Discussionmentioning
confidence: 99%
“…This analysis used secondary data from a cross-sectional study nested within a large-scale community-based HIV prevention program, called the Sauti Project [ 19 , 29 , 30 ], funded by the U.S. President’s Emergency Plan for AIDS Relief/U.S. Agency for International Development, to reach vulnerable and high-risk populations in Tanzania.…”
Section: Methodsmentioning
confidence: 99%
“…Studies in South Africa reported lifetime experience of gender-based violence (GBV) is associated with HIV risk acquisition [ 16 18 ]. Additionally, in the Southern Highlands of Tanzania and Uganda, an association between alcohol consumption before sex and the risk of HIV infections was reported [ 11 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…We identified 12 ongoing studies: 10 of these studies are being conducted in adolescent populations, 9 of which focus on adolescent girls and young women (S2 Table) [59][60][61][62][63][64][65][66][67][68][69]. All 8 of the interventions include adolescents are in sub-Saharan Africa (Ghana, South Africa (N = 4), Zimbabwe, Kenya (N = 2), Malawi, Uganda, and Tanzania).…”
Section: Ongoing Studiesmentioning
confidence: 99%